Active faults of the world - Yeats, Robert S. (Cambridge University Press, 2017)
"Active Faults of the World There is an ever increasing need for a better understanding of regional seismic hazards, particularly in developing parts of the world where major building projects are planned and there is a huge migration of people to large cities that are at risk from earthquakes. Disasters in recent times, such as the earthquakes in Japan and Haiti, are chilling proof of the dangers of building in active fault zones"--